EFFECTS OF TOGETHER LEARNING ON UNIVERSITY STUDENTS TO ACHIEVEMENT MOTIVATION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The purpose of this paper is to describe the effects of Together Learning (TL) on the achievement motivation of college students, as well as to compare the achievement motivation of physical education students learning basic tennis skills via Together Learning versus those using the traditional learning method. In this study, an intervention approach was designed as part of a novel learning method to encourage the performance of physical education, and students (average age =20.3 years, N= 60) were encouraged to participate as part of their physical education classes to learn fundamental tennis abilities. The survey was administered as a pre-test at the start of therapy for both the treated and control groups. The Achievement Motive Scale (AMS) was used in this study, as well as the Hewitt test to basic tennis abilities and as post-tests at the conclusion of 10 weeks. The T-test was performed to determine whether there were statistically significant differences in achievement motivation across the groups. Conclusions and Suggestions: According to the data, the jointly learning classes boost college physical education students' accomplishment motivation and basic tennis skill acquisition